Fully bio-based zwitterionic membranes with superior antifouling and antibacterial properties prepared via surface-initiated free-radical polymerization of poly(cysteine methacrylate). Issue 34 (17th August 2018) - Valencia, Luis; Kumar, Sugam; Jalvo, Blanca; Mautner, Andreas; Salazar-Alvarez, German; Mathew, Aji P.
Abstract : This article proposes a strategy to prepare membranes that combine the network characteristics of micro/nanocellulose with grafted zwitterionic PCysMA to develop fully bio-based membranes with antifouling properties. Abstract : This article proposes a strategy to prepare membranes that combine the network characteristics of micro/nanocellulose with grafted zwitterionic poly(cysteine methacrylate) (PCysMA) to develop fully bio-based membranes with antifouling properties. The surface characteristics of the membranes were studied, together with static adsorption of bovine serum albumin (BSA) and S. aureus for evaluating the antifouling properties of the membranes. Experimental data revealed a homogeneous modification that resulted in excellent antifouling properties with a reduction of 85% in biofilm formation and enhanced antimicrobial activity. Moreover, we introduced a novel method to determine the pore size of membranes in the wet-state and assess the antifouling performance in situ by synchrotron-based SAXS. This allowed us to observe in real-time the decrease in pore size upon adsorption of BSA during filtration, and how this phenomenon is strongly suppressed by grafting of PCysMA. The importance of this work lies in introducing a simple method to yield cellulosic membranes with superior antifouling properties, which could significantly increase their potential for water treatment applications.